Conjoined twins in a triplet pregnancy: A rare obstetrical dilemma - Ozcan, Huseyin C. (Saudi Med J, 2017)
Conjoined twins are derived from division of a single fertilized ovum after the twelfth day of fertilization. Triplet conjoined twin is considered as a unique phenomenon that is accompanied with a wide variety of congenital abnormalities and also hazardous consequences for both fetuses and parents. We present an extremely rare case of conjoined twins in a triplet pregnancy with symmetric thoracoomphalopagus that was diagnosed in prenatal period by using ultrasound scanning and MRI. In triplet pregnancies, we should be aware about the possibility of conjoined twins. If there are severe congenital malformations, termination of pregnancy should be recommended immediately after the diagnosis regardless of gestational age, particularly in early gestational age.